Differences in the oral health behaviour of the 12-years-old children in rural and urban areas - Nawawi, Azkya Patria; Fadillah, Rina Putri Noer; Supriatna, Andi; Sarwendah, Sri (Universitas Padjadjaran, 2017)
Introduction: The oral diseases have increased significantly in the past decade. The Health Service of Cimahi reports showed an increasing number of oral diseases. Behaviour plays an important role in preventing oral disease. The purpose of this study was to examine the differences in the oral health behavior of the 12-years-old children in the rural and urban area of the city of Cimahi. Methods: The research type was analytic with the cross-sectional design. The sample was determined using pathfinder survey method from oral health surveys basic methods. Data were collected through a questionnaire containing knowledge and attitudes, observations of practice assessed in the checklist and assessment of the health status of the teeth using the Patient Hygiene Performance Data Index and analyzed using the Mann-Whitney test. Results: The results showed that children in both rural and urban areas were having a good knowledge and positive attitude. Both the rural and urban children were doing the improper tooth brushing methods, and the children in the rural area had a fair PHP index value whilst the children in the urban area had a poor value. There were significant differences in the knowledge (p = 0.017), there was no significant difference in the attitude (p = 0.312) and practice (p = 1.000) in children of both rural and urban areas. Conclusion: Difference only found in the oral health knowledge of the 12-years-old children in the rural and urban area of the city of Cimahi.